Muscle oximetry in sports science: an updated systematic review - Perrey, S.; Quaresima, V.; Ferrari, M. (Sports Medicine, 2024)
Background: In the last 5 years since our last systematic review, a significant number of articles have been published on the technical aspects of muscle near-infrared spectroscopy (NIRS), the interpretation of the signals and the benefits of using the NIRS technique to measure the physiological status of muscles and to determine the workload of working muscles.